2023
DOI: 10.1186/s13229-023-00565-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of chronic physical health conditions across all organ systems in autistic adolescents and adults

John H. Ward,
Elizabeth Weir,
Carrie Allison
et al.

Abstract: Background The poorer physical health of autistic adults compared to non-autistic adults has been highlighted by several epidemiological studies. However, research has so far been limited to specific geographical areas and has primarily focused on young autistic individuals (aged 35 years and younger). Recent studies indicate a higher rate of mortality in autistic people, as well as poorer quality of self-reported healthcare interactions. This study aims to determine, first, whether autistic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
0
0
1
Order By: Relevance
“…It is possible that these issues are also gender related, since women tend to be underdiagnosed (Begeer et al, 2013;Loomes et al, 2017) whereas CSS are more commonly recognised in women compared to men (Lawrence et al, 2008). Whilst there is a demonstrable overlap in physical symptoms between autism and CSS, the results of this study, and other recent studies (Ward et al, 2023), suggest that the CSI and AQ are both working reliably and consistently to identify symptoms of central sensitisation and autistic traits, and that there are increased rates of central sensitivity symptoms and diagnoses in autistic adults.…”
Section: Hierarchical Regression and Path Analysissupporting
confidence: 40%
See 3 more Smart Citations
“…It is possible that these issues are also gender related, since women tend to be underdiagnosed (Begeer et al, 2013;Loomes et al, 2017) whereas CSS are more commonly recognised in women compared to men (Lawrence et al, 2008). Whilst there is a demonstrable overlap in physical symptoms between autism and CSS, the results of this study, and other recent studies (Ward et al, 2023), suggest that the CSI and AQ are both working reliably and consistently to identify symptoms of central sensitisation and autistic traits, and that there are increased rates of central sensitivity symptoms and diagnoses in autistic adults.…”
Section: Hierarchical Regression and Path Analysissupporting
confidence: 40%
“…Joint hypermobility disorders and the Ehlers-Danlos syndromes (EDS) are often found to underly CSS diagnoses (Csecs et al, 2022;J. Eccles et al, 2020;Sharp et al, 2021), and autistic women in particular are more likely to be diagnosed with EDS than the general population (Casanova et al, 2020;Ward et al, 2023). There is also some research suggesting that sensory sensitivity is directly related to connective tissue differences (Casanova et al, 2020;Colman et al, 2023;Csecs et al, 2022;Savage et al, 2021).…”
Section: Hierarchical Regression and Path Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research points to high rates of most major psychiatric disorders and chronic medical conditions among autistic adults, including depression, anxiety, psychoses, obsessive-compulsive disorder (OCD), bipolar disorder, and attention deficit disorder as well as hyperlipidemia, epilepsy, sleep disorders, obesity, diabetes, cardiovascular disease, and hypertension (Bishop et al, 2021; Bishop-Fitzpatrick & Rubenstein, 2019; Broder-Fingert et al, 2014; Buck et al, 2014; Croen et al, 2015; McLean et al, 2021; Tyler et al, 2011). Most recently, research has found that autistic adults may have a higher risk of cardiometabolic diseases, central sensitivity syndromes, Parkinson’s disease, gastrointestinal issues, and most other non-communicable diseases (Dhanasekara et al, 2023; Grant et al, 2022; Hand et al, 2020; Ward et al, 2023). Determining the mechanisms underlying the high prevalence of poor health outcomes in autistic adults requires better understanding of the lived experiences of autistic adults across the adult lifespan.…”
unclassified